Experimental study on thermal performance of a novel medium-high temperature packed-bed latent heat storage system containing binary nitrate. (1st March 2022) - Wang, Wei; He, Xibo; Shuai, Yong; Qiu, Jun; Hou, Yicheng; Pan, Qinghui
Highlights: A novel medium-high temperature PBLHS system is designed and constructed. The thermal efficiency of the initial stage of the heat storage and release process is higher. The overall efficiency of the PBLHS system based on binary nitrate is 79.3%. The temperature and flow rate of the air has a significant effect on the pressure loss of the PBLHS system. Abstract: The packed-bed latent heat storage (PBLHS) system has received extensive attention due to its low investment cost and good application prospects. In the past, the research on this system mainly focused on the establishment of mathematical models and the structural optimization of the thermal energy storage (TES) tank. There are few experimental studies on the thermal performance of PBLHS systems under medium-high temperature conditions. In this work, a novel medium-high temperature PBLHS experimental system is designed and constructed. Based on binary nitrate NaNO3 –KNO3 (55-45 wt%) as the phase change materials (PCM), a spherical encapsulated PCM suitable for the packed bed TES is prepared. The heat transfer characteristics of the charging process, the static heat preservation process, and the discharging process are experimentally studied, respectively. In addition, the influence of the temperature and flow rate of the heat transfer fluid on the pressure drop of the PBLHS system is also investigated. The results indicate that with the continuous increase of the average air temperature inside the TES tank, the temperature difference inside the tank shows a trend of first increasing and then decreasing. When the average air temperature is around 225–272 ℃, the temperature difference is almost at a stable stage, and the temperature difference is about 84 ℃ (±1 ℃). The temperature difference decreases slowly in the initial stage of the discharging process. The overall efficiency of the current PBLHS system based on binary nitrate is 79.3%. The results also indicate that the air temperature and flow rate have a significant effect on the pressure loss of the packed-bed system. The experimental results of this work can provide experimental data support for the structural optimization design and industrial application of the packed-bed TES system.